Pengaruh Faktor Keperilakuan Organisasi Terhadap Sistem Akuntansi Keuangan Daerah Pada Badan Pengelola Keuangan Dan Aset Daerah Kabupaten Sikka - Marlince Dipi Gapa; Henrikus Herdi; Yoseph Darius Purnama Rangga (Universitas Katolik Widya Karya Malang, 2023)
This study aims to determine and examine the influence of organizational behavior factors on the implementation of the regional financial accounting system. This type of research is descriptive and quantitative research. The population in this study was the total number of employees divided into several divisions with a total of 51 employees. The sampling technique used was to use saturated sampling with the number of samples used was as many as 41 respondents taken based on questionnaires that returned. Data collection was carried out using questionnaires measured with Likert scales. The analysis methods used are Multiple Linear Regression Analysis, T Hypothesis Test, F Hypothesis Test and Coefficient of Determination. The results of this study show that superior support and training do not affect the implementation of the regional financial accounting system while the clarity of objectives has a positive effect on the implementation of the regional financial accounting system.